2018
DOI: 10.1007/s10858-018-0190-5
|View full text |Cite
|
Sign up to set email alerts
|

Methyl group reorientation under ligand binding probed by pseudocontact shifts

Abstract: Liquid-state NMR spectroscopy is a powerful technique to elucidate binding properties of ligands on proteins. Ligands binding in hydrophobic pockets are often in close proximity to methyl groups and binding can lead to subtle displacements of methyl containing side chains to accommodate the ligand. To establish whether pseudocontact shifts can be used to characterize ligand binding and the effects on methyl groups, the N-terminal domain of HSP90 was tagged with caged lanthanoid NMR probe 5 at three positions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…The STD method can also provide useful information regarding clients bound to large chaperone systems . The PCS and RDC techniques have been applied in characterizations of chaperones either in their apo‐states or in complex with ligands . Furthermore, solid‐state NMR methods have also been recently successfully applied in the study of amyloids interactions with the chaperonin GroEL system …”
Section: Discussionmentioning
confidence: 99%
“…The STD method can also provide useful information regarding clients bound to large chaperone systems . The PCS and RDC techniques have been applied in characterizations of chaperones either in their apo‐states or in complex with ligands . Furthermore, solid‐state NMR methods have also been recently successfully applied in the study of amyloids interactions with the chaperonin GroEL system …”
Section: Discussionmentioning
confidence: 99%
“…The utility of rapid, accurate methyl assignments is highlighted by recent studies that used NOEs between an unlabeled ligand and a methyl-labeled protein as restraints to generate models of the docked complex 32,41,53,54 and PCSs to measure reorientation of methyl groups upon ligand binding. 55 In the future, MethylFLYA could be extended to incorporate paramagnetic restraints, such as PREs or PCSs, or be combined with existing software packages that predominantly rely on these restraints. 26,27 Furthermore, MethylFLYA can straightforwardly be used to assign methyl resonances in solid-state NMR spectra.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the Ln 3+ ion and ∆χ-tensor were calculated with Numbat [22] using the crystal structure of the MPS1 TPR domain (PDB entry, 4H7Y) [21] and the PCSs for residues 59-199. The quality (Qa) scores of PCSs were calculated as previously described [23], using the following formula.…”
Section: Nmr Measurements Assignment and Data Analysismentioning
confidence: 99%
“…We have previously speculated that the interaction of the NTE module with the TPR exerts an auto-inhibitory function to the NTE, moderating the interaction with the NDC80C complex in the outer kinetochore [6]. Subsequently, an NMR analysis including the assignment of most amide resonances (87%) of the NTE-TPR module, showed that the NTE does not adopt a defined structure, except for a short segment (residues, [14][15][16][17][18][19][20][21][22][23], which has a propensity to form a helical turn [7]. This helical fragment is required for interactions with kinetochores and forms intermolecular interactions with the TPR domain.…”
Section: Introductionmentioning
confidence: 99%